Mycobacterium tuberculosis requires glyoxylate shunt and reverse methylcitrate cycle for lactate and pyruvate metabolism. Issue 4 (23rd August 2019) - Serafini, Agnese; Tan, Lendl; Horswell, Stuart; Howell, Steven; Greenwood, Daniel J.; Hunt, Deborah M.; Phan, Minh‐Duy; Schembri, Mark; Monteleone, Mercedes; Montague, Christine R.; Britton, Warwick; Garza‐Garcia, Acely; et al.
Summary: Bacterial nutrition is an essential aspect of host–pathogen interaction. For the intracellular pathogen Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis in humans, fatty acids derived from lipid droplets are considered the major carbon source. However, many other soluble nutrients are available inside host cells and may be used as alternative carbon sources. Lactate and pyruvate are abundant in human cells and fluids, particularly during inflammation. In this work, we study Mtb metabolism of lactate and pyruvate combining classic microbial physiology with a 'multi‐omics' approach consisting of transposon‐directed insertion site sequencing (TraDIS), RNA‐seq transcriptomics, proteomics and stable isotopic labelling coupled with mass spectrometry‐based metabolomics. We discovered that Mtb is well adapted to use both lactate and pyruvate and that their metabolism requires gluconeogenesis, valine metabolism, the Krebs cycle, the GABA shunt, the glyoxylate shunt and the methylcitrate cycle. The last two pathways are traditionally associated with fatty acid metabolism and, unexpectedly, we found that in Mtb the methylcitrate cycle operates in reverse, to allow optimal metabolism of lactate and pyruvate. Our findings reveal a novel function for the methylcitrate cycle as a direct route for the biosynthesis of propionyl‐CoA, the essential precursor for the biosynthesis of the odd‐chain fatty acids. Abstract : Mycobacterium tuberculosis assimilates lactate and pyruvate utilising glyoxylate shunt and methylcitrate cycle, two pathways traditionally associated with fatty acid metabolism in bacteria. Surprisingly, we found that M. tuberculosis synthesises propionyl‐CoA by a reverse methylcitrate cycle and another partially characterised (in this study) pathway. Our results point to a re‐interpretation of the mechanistic role and utilisation of these pathways by Mtb during infection, i.e., their potential reversibility and importance during lactate and pyruvate metabolism in vivo .